Eksistensi Cerita Rakyat dalam Pendidikan Karakter Siswa SD di Ubud - Ni Putu Parmini (Pusat Kajian Bali Universitas Udayana, 2015)
AbstractBalinese folktales should be preserved and developed in order to improve the emotional intelligence of the nation, especially elementary school children as the future generation. This article analyses the existence of Balinese folktales in character education in elementary school children in Ubud. The study on the use of folktales shows that Balinese folktales contributed to character education in elementary school children. It was shown in the folktale I Lacur which educates cautionary acts, not being envious, being stoical and helpful. The folktale Bulan Kuning also contributes to the formation of the attitude of helpfulness. Stoicism and not doing violence are narrated in the folktale Ni Tuung Kuning which can be used as an alternative in the improvement of children’s character. The folktale I Crucuk Kuning contributes to the formation of honesty, discipline, and responsibility. The folktale Angsa teken I Kekua contributes to the formation of attitudes of not breaking a promise. The use of folktale in teaching not only useful in passing on moral values of the stories but also to preserve the intangible cultural heritage.